A Multimodal Approach to the Audio Recording of Written Scripture - Winedt, Marlon (2025)
This article explores the audio recording of written Scripture as a distinct communication mode where the voice functions not merely as a vehicle of meaning but as a semiotic resource to create meaning. A social-semiotic resource, as developed by Kress and van Leeuwen, is defined by the multimodal nature of communication, integrating linguistic, sensory, and sociocultural dimensions.Bible translation often emphasizes the implementation of linguistic and literary textual analysis of the source text(s) but can benefit from including a greater focus on voice as an expression of social-semiotic identity—culturally specific yet universally significant. Voice elements like tonality, pitch, timbre, volume, and speed serve as semiotic markers in non-written texts, requiring careful consideration during preparation, review, and translation consultation. Translation teams should integrate these aspects into their work to enhance the performative quality and cultural relevance of oral and audio renditions without unduly burdening the project in a minority-language situation. There is a need to work in interdisciplinary teams to produce high-quality multimodal translations.
Keywords: creolistics; recording of written Scripture; social semiotics; Orality; Bible Translation; Multimodality